2017
DOI: 10.1016/j.bbrep.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the efficacy of pulsed electromagnetic field and low level laser therapy on mitogen-activated protein kinases

Abstract: Mitogen-Activated Protein Kinases (MAPKs) consist of three major signaling members: extracellular signal-regulated kinase (ERK), p38 and C-JUN N-terminal kinase (JNK). We investigated physiological effects of Pulsed Electromagnetic Field Therapy (PEMFT) and Low Level Laser Therapy (LLLT) on human body, adopting the expression level of mitogen-activated protein kinases as an indicator via assessment of the activation levels of three major families of MAPKS, ERK, p38 and JNK in the peripheral lymphocytes of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Expression levels of MAPK was determined in peripheral lymphocytes. The findings indicated that there was a significant increase in ERK expression levels but not in the expression levels of p38 and JNK [102].…”
Section: Immortalised Granulosa (Kgn) Cellsmentioning
confidence: 86%
See 1 more Smart Citation
“…Expression levels of MAPK was determined in peripheral lymphocytes. The findings indicated that there was a significant increase in ERK expression levels but not in the expression levels of p38 and JNK [102].…”
Section: Immortalised Granulosa (Kgn) Cellsmentioning
confidence: 86%
“…VEGF is a potent pro-neoangiogenic cytokine [109], essential for neovascularization during the wound restorative process [101]. In another study, El-Makakey et al [102] conducted a comparative study monitoring the physiological effects of pulse electromagnetic field therapy (PEMFT) and PBM on the human body. They reported on the use of a pulsed wave diode laser at a wavelength of 905 nm with an impulse duration of 100 ns and a peak power of 25 W. The 25 patients to whom PBM alone was applied were subjected to the treatment twice daily for six successive days at the site of the appendectomy wound (3-4 cm).…”
Section: Immortalised Granulosa (Kgn) Cellsmentioning
confidence: 99%